Carbon-coating effect on the performance of photolithographically-structured Si nanowires for lithium-ion microbattery anodes - Andam Deatama Refino; Nursidik Yulianto; Slamet Priyono; Maykel Manawan; Rahmandhika Firdauzha Hary Hernandha; Egy Adhitama; Jonathan Kottmeier; Andreas Dietzel; Erwin Peiner; Hutomo Suryo Wasisto (Communications Materials)
Abstract The applications of three-dimensional Si nanowire anodes in lithium-ion microbatteries have attracted great interest in the realization of high-capacity and integrated energy storage devices for microelectronics. Combining Si nanowires with carbon can improve the anode performance by aiding its mechanical stability during cycling. Here, we incorporate photolithography, cryogenic dry etching, and thermal evaporation as the commonly used methods in semiconductor technologies to fabricate carbon-coated Si nanowire anodes. The addition of amorphous carbon to Si nanowire anodes has an impact on increasing the initial areal capacity. However, a gradual decrease to 0.3 mAh cm−2 at the 100th cycle can be observed. The post-mortem analyses reveal different morphologies of Si nanowire anodes after cycling. It is indicated that carbon coating can help Si nanowires to suppress their volume expansion and reduce the excessively produced amorphous Si granules found in pristine Si nanowire anodes.